2015
DOI: 10.1093/mmy/myv069
|View full text |Cite
|
Sign up to set email alerts
|

Th17 and regulatory T cells contribute to thein situimmune response in skin lesions of Jorge Lobo's disease

Abstract: Jorge Lobo's disease (JLD) is a chronic granulomatous mycosis described in various Latin American countries. The main objective of the present study was to investigate the possible role of Th17 and Foxp3+ Treg cells in the pathogenesis of Jorge Lobo's disease. Human skin biopsies were submitted to an immunohistochemistry protocol to detect Foxp3, interleukin (IL)-1beta, CD25, IL-6, IL-17, and IL-23. The epidermis presented acanthosis, hyperkeratosis, and frequent presence of fungi. The dermis presented inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
4
0
4
Order By: Relevance
“…Some studies showed that Tregs increased protective immunity (Pandiyan et al, 2011, Netea et al, 2004, Schulze et al, 2014, Wiesner et al, 2016, while in other models, Tregs promoted fungal infection (Felonato et al, 2012;Whibley et al, 2014). Our results suggest that, in addition to the immunosuppressive role of Tregs in avoiding excessive inflammation, they may also favor a shift to a Th17 response, promoting the elimination of the pathogen in advanced stages of infection (Kanashiro-Galo et al, 2016;Sehrawat and Rouse, 2017). The effect of Tregs on the Th17 function in fungal infection is also controversial.…”
Section: S Brasiliensismentioning
confidence: 74%
“…Some studies showed that Tregs increased protective immunity (Pandiyan et al, 2011, Netea et al, 2004, Schulze et al, 2014, Wiesner et al, 2016, while in other models, Tregs promoted fungal infection (Felonato et al, 2012;Whibley et al, 2014). Our results suggest that, in addition to the immunosuppressive role of Tregs in avoiding excessive inflammation, they may also favor a shift to a Th17 response, promoting the elimination of the pathogen in advanced stages of infection (Kanashiro-Galo et al, 2016;Sehrawat and Rouse, 2017). The effect of Tregs on the Th17 function in fungal infection is also controversial.…”
Section: S Brasiliensismentioning
confidence: 74%
“…While macrophages and fibroblasts may be responsible for IL-17 expression in the lesions [ 49 , 50 , 51 ], the putative inhibitory effect that Tregs have on Th17 cells may be critical in preventing the development of comprehensive Th17 responses in the lesions. A recent study demonstrated that IL-17+ cells outnumbered FOXP3+ cells in JLD lesions [ 52 ]. This report is consistent with the findings regarding IL-17 and FOXP3 expression in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This report is consistent with the findings regarding IL-17 and FOXP3 expression in the present study. However, the previous authors concluded that high levels of Th17 cytokines could overcome the effects of Treg cells [ 52 ]. This assertion does not consider the fact that Tregs make up a very small fraction of lymphocyte subsets both, in the circulating lymphocytes pool and in inflammatory infiltrates in peripheral tissues; it is not surprising that effector cells, such as IL-17+ cells, may outnumber FOXP3+ cells [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ineffective immune response against the agent seems to be related to a Th2-type cytokines pattern and the lesions comprise a clinical and immunological spectrum that varies from susceptible to resistant to treatment 5 . In addition, an expressive number of IL17-producing CD4+ T cells over TCD4+ Foxp3+ in lacaziosis skin lesions have been described, and it is suggested that the Th17 cytokine pattern may be present as an auxiliary mechanism for modulating the local immune response 6 . The cytotoxic function of CD8+ T cells was evidenced based on the detection of perforin and granzyme B and a role in the in situ immune response to eliminate the fungus was suggested.…”
Section: Introductionmentioning
confidence: 99%